Analisis Kelayakan Usaha Dan Strategi Pengembangan Industri Kecil Keripik Cinta Mas Hendro Di Kecamatan Gebang Kabupaten Langkat - Ayu Rahmatunnisa, Kamaliah R, Diyan Yusri (Islamic Education Journal, 2023)
Marketing Strategies in Increasing Clothing Sales at 35,000 Convenience Stores in Tanjung Pura Subdistrict, Langkat Regency According to the Syariah Economy Perspective. The research method used in this study is a descriptive qualitative research method with an empirical approach. After the researchers conducted research by interviewing, observing, and documenting, it was concluded that: The marketing strategy applied at the 35,000 Convenience Store in Tanjung Pura District, Langkat Regency is a market segmentation strategy, targeting, positioning and differentiation. In the application of market segmentation, 35,000 Convenience Stores compile market segments with 4 segments. Among them are geographical segmentation, demographic segmentation, psychographic segmentation and behavior segmentation. Factors supporting the marketing strategy are strategic location, support from the surrounding community. good management, honest employees, good service, while the factors inhibiting the marketing strategy are employee shortages and delays in future items. The implementation of the sharia marketing strategy by the 35,000 Convenience Store in Tanjung Pura Subdistrict, Langkat Regency is conducted to comply with religious teachings and so as not to act out of the norms of religious law. Services that are in accordance with the characteristics of sharia marketing are also implemented so that employees continue to work professionally and remain realistic in providing services and do not differentiate from the surrounding community caste. The effort was made in order to maintain kinship to the surrounding community so that they can still be good partners and can also increase trust in the 35,000 Convenience Store.